A life in human rights: a conversation with Dennis Davis. Issue 1 (28th June 2021) - Krever, Tor
Abstract: Dennis Davis is Judge of the High Court of South Africa, Judge President of the Competition Appeal Court, and Honorary Professor of Law at the University of Cape Town. In this wide-ranging conversation with Tor Krever, he reflects on his political and intellectual trajectory—from early encounters with Marx to anti-apartheid activism to a leading position in the South African judiciary—and his lifelong commitment to a radical left politics.